Behavioural responses of male ruffed grouse (Bonasa umbellus, L.) to playbacks of drumming displays. (21st January 2018) - O'Neil, Nicholas P.; Charrier, Isabelle; Iwaniuk, Andrew N.
Abstract: Birds use a variety of sounds in their courtship displays, but the majority of behavioural studies have focused on vocalizations. In contrast, little is known about how non‐vocal sounds, or sonations, are used, even though many avian species produce them. The ruffed grouse ( Bonasa umbellus ) is a useful species to examine non‐vocal sounds because they lack vocal components in their courtship and rely on a non‐vocal sound to attract mates and defend their territory. Their courtship display, known as "drumming, " is created by the wings, and the number of pulses and speed (pulse rate) varies significantly among males. Anecdotal evidence suggested that males can affect the drumming behaviour of neighbouring males in drumming "duels" in an analogous way to song contests. Here, we test whether males do respond to the playback of drumming sounds of an unfamiliar male. Using a portable speaker system, we played recordings of drumming displays to males that were actively drumming themselves. Throughout each playback, we recorded the drumming behaviour of target males so that we could assess whether drumming activity changes following a playback as well as whether males change the speed of their display. Overall, male grouse were equally likely to approach the speaker or continue drumming following a playback. For those males that continued drumming, their drumming pulse rate was significantly faster following playbacks, but they drummed less often. These results indicate that male ruffed grouse do respond to drumming sounds, but the specific response differs among males. Because the differential response was not related to colour phase or whether a male was drumming in proximity to other males, we suggest that the response of individuals likely varies with other traits, such as hormone levels or behavioural syndrome.